Projeto de uma residência unifamiliar sustentável em condomínio de alto padrão em Parnamirim/RN - Barbosa Júnior, Juarez de Quadros (2017)
Sustainability has gained strength and has driven several studies in the most varied areas, be it architecture, environment, education, economics or public administration. The paper addresses issues to the development and revenue of sustainability issues in single family homes, specifically the use of renewable natural resources, environmental comfort concerns and energy efficiency in the process and reduction of wastage of materials during construction of the building. The present work aims to elaborate a project of a sustainable single family dwelling in condominium of high standard, in hot and humid climate, with a maximum efficiency of the renewable resources, with a capture of solar energy and rainwater, besides the use of a Modulation and frames that allow a permeability of the winds and the direct solar radiation with control of the user during the periods of summer and winter. During the studies, the concept of hive was used, through its modalities, rationalization, and appropriation of space, adapting to one of the structures that shows great balance in nature, since it is sustainable without conflicts between spaces. Or surroundings. The main constraints for a proposal or bioclimatic zoning, such as urbanistic prescriptions for the region under study, a use of standardized modulation, volumetric and situational studies to meet the program needs and rationalization of production processes, obvious solutions solutions for improvement in The Allocation of natural resources - rational use of water and reuse of rainwater and renewable energies, in agreement with the feasible cost of implementation. The proposed single-family residence project with 507.60m² resulted in lower environmental impact in addition to a positive impact in reducing operating and maintenance costs, making its construction and operation more feasible than a conventional residence.